Evaluation of in vitro experimental model for analysis of bioceramic sealers - Ericke Mucke SILVA; Murilo Priori ALCALDE; Rodrigo Ricci VIVAN; Marcelo POMINI; Mario TANOMARU-FILHO; Marco Antonio Hungaro DUARTE (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study aimed to evaluate physicochemical properties of three ready-to-use calcium silicate-based endodontic sealers: Endosequence BC Sealer, Bio C Sealer, and Sealer Plus BC. Radiopacity was evaluated using specimens of 10 mm in diameter and 1 mm in height, along with an aluminum step wedge. For the flow test, 0.5 mL of each sealer was deposited between glass plates and the mean of the measurement of two diameters was considered the cement flow value. For pH and calcium release, root canals of 30 prototypes of upper incisor acrylic resin teeth were filled with sealer and gutta percha point and then immersed in containers with 13 mL of ultrapure water. Both pH and release of calcium ions (atomic absorption spectrophotometer) were measured at 3, 24, 72, and 168 h. Acrylic resin teeth were scanned by Micro-CT 1174 at the time of pH and calcium ion readings for volumetric change analysis. The data were analyzed by ANOVA, Tukey's, Kruskal-Wallis, and Dunn's tests. Endosequence BC Sealer presented the lowest, and Bio C Sealer the highest volumetric change after 72 h and 168 h (p < 0.05). Endosequence BC Sealer presented higher radiopacity (p < 0.05). All materials showed alkalinization capacity. All of them presented calcium ion release, with a higher value for Sealer Plus BC. All materials presented alkalinization, calcium release capacity, radiopacity, and flow above the minimum values required by the ISO standard. The highest volumetric loss was experienced by Bio C Sealer and the lowest one by Endosequence BC Sealer.